2017
DOI: 10.3390/d9040047
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Invasion of Weakfish Cynoscion regalis (Bloch & Schneider, 1801) (Actinopterygii: Sciaenidae) into Europe

Abstract: New information on weakfish

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Finally, the collaboration of scientists with local fishers and the general public must be encouraged to anticipate the detection of new species, as has already occurred for the oceanic puffer (this study), the weakfish Cynoscion regalis (Bloch and Schneider, 1801), and the Atlantic blue crab Callinectes sapidus Rathbun, 1896 [62][63][64]. These experiences perfectly illustrate the importance of citizen-science initiatives in the advance of Marine Ecology.…”
Section: Discussionmentioning
confidence: 65%
“…Finally, the collaboration of scientists with local fishers and the general public must be encouraged to anticipate the detection of new species, as has already occurred for the oceanic puffer (this study), the weakfish Cynoscion regalis (Bloch and Schneider, 1801), and the Atlantic blue crab Callinectes sapidus Rathbun, 1896 [62][63][64]. These experiences perfectly illustrate the importance of citizen-science initiatives in the advance of Marine Ecology.…”
Section: Discussionmentioning
confidence: 65%
“…Callinectes sapidus Rathbun, 1896 [61][62][63]. These experiences clearly highlight the importance of citizen-science initiatives.…”
Section: Discussionmentioning
confidence: 98%
“…Second, cherish the contributions from informed citizens and strengthen that partnership. The records provided by informed citizens on non-indigenous and uncommon species are precious information that often ignites research efforts (Morais et al, 2017;Morais et al, 2019), so they must be encouraged. However, given the sporadic nature of such records, they must be part of a broader effort to complement citizen science projects and scientific research.…”
Section: Discussion a Roadmap To Citizen Science Successmentioning
confidence: 99%
“…For example, the first record of weakfish Cynoscion regalis (Animalia, Perciformes) in southern Portugal was reported by a fisherman to scientists (Morais and Teodósio, 2016). This led to the development of a citizen science project-through social media and traditional media-which revealed that the species was going unnoticed by the scientific community for years in several locations across Portugal (Morais et al, 2017). Similarly, the first record of Asian bush mosquito Aedes japonicus (Animalia, Diptera) in Spain was submitted to the project "Mosquito Alert", triggering scientific surveys that confirmed the presence of the species and suggesting that the establishment had occurred a long time ago (Eritja et al, 2019).…”
Section: Records Of Non-indigenous Species Made By Informed Citizensmentioning
confidence: 99%
See 1 more Smart Citation